From flowers to pollinators: Dietary exposure of honey bees, bumble bees and solitary bees to trace elements across European fields - Maciej Durkalec; Agnieszka Nawrocka; Petru Jitaru; Marie-Pierre Chauzat; Marion Laurent; Matthias Albrecht; Cecilia Costa; Pilar De la Rúa; Alexandra-Maria Klein; Marika Mänd; Simon G. Potts; Maj Rundlöf; et al. (Journal of Hazardous Materials, 2026)

Synthesis strategies, nutrient delivery mechanisms, and pathways toward sustainable agriculture via nano-fertilizers - Praveen Mallari; Venkatachalam Deepa Parvathi; V. Sathishkumar; R. B. Jeen Robert; M. Joemax Agu; M. Muthuselvi; G. S. Hikku (Journal of Crop Science and Biotechnology, 2026)

Effect of Carbohydrate-Restricted Dietary Patterns Based on Prescribed and Self-Reported Intake in Adults with Overweight and Obesity: A Systematic Review and Meta-Analysis - Matthew Landry; Mary R. Rozga; Tami Piemonte; Amy M. Goss; Kerri L. Knippen; Justin A. Robinson; Dana M. Scheunemann; Deepa Handu (Journal of the Academy of Nutrition and Dietetics, 2026)

Marine heatwaves alter shell microbiomes and denitrification capacity: An oyster family-specific response - Giulia Filippini; Ana B. Bugnot; Wayne O'Connor; Paul E. Gribben; Deepa R. Varkey; Ian T. Paulsen; Katherine A. Dafforn (Marine Pollution Bulletin, 2026)

Enhancing Oryza sativa Growth with a Genome-Characterized Bacillus velezensis SNR14-4, a Marine Strain Isolated from Fish Gills - Nambillipadath R. Rashid Muhammed; Sethu Madhavan; Niveditha D. Neroth; Deepa John; Sini Hariharan; Kottayath G. Nevin (Agricultural Research, 2026)

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

Exploring the role of MOFs in enhancing the durability of construction materials - Deepa Mundekkad; Anjali R. Mallya; William C. Cho (Arabian Journal of Geosciences, 2025)

Spectroscopic Analysis of 4-MeO-TPA with Metal Oxide Nano-Assembly: Insights on Fluorescence Quenching and FRET - V. V. Koppal; R. Venkatesh; N. R. Banapurmath; Kalpana Sharma; Deepa H. K (Journal of Fluorescence, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Experimental investigation of shrouded tomato storage systems in mitigating losses during long-distance transportation - G. Hari Pranesh; S. Ganga Kishore; P.L. Meenakshi; V. Arun Prasath; Madhuresh Dwivedi; J. Deepa; R. Pandiselvam; M. Arulkumar (Journal of Stored Products Research, 2025)

Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

Effects of short term dietary zinc deficiency and zinc supplementation on nitro-oxidative stress in testes of Wistar rats - Deepa Kumari; Neena Nair; R. S. Bedwal (BioMetals, 2025)

Molecular Detection of Benzimidazole Resistance Associated with the F200Y Polymorphism in the β-Tubulin Gene of Ancylostoma caninum: First Report from India - Deepa Soman; R. Radhika; Bindu Lakshmanan; Asha Rajagopal; M. N. Priya; K. Syamala; Arun George (Acta Parasitologica, 2025)

Unique humoral immune response of pigs to repeated natural Japanese encephalitis virus infections: an amplifying host perspective - M. Dhanalakshmi; Himani Dhanze; Akash Mote; N. Narmatha; K. Sibi Thomas; R. Nithiaselvi; Deepa Mehta; M. Suman Kumar; K. N. Bhilegaonkar (Archives of Virology, 2025)

Genetic diversity and population structure analysis in tamarind (Tamarindus indica L.) using SCoT and SRAP markers - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; D. C. Lakshmana Reddy; K. Prakash (Genetic Resources and Crop Evolution, 2025)

Clinicopathological findings and etiological characterization in caprine gangrenous mastitis - Nikhija.S. Anil; A. Janus; P.M. Deepa; V.H. Shyma; R. Rajasekhar; Biju.P. Habeeb; Lali F. Anand (Small Ruminant Research, 2024)

Bimetallic/Cellulose nanohybrids: A flexible, versatile, and sustainable biomaterial - Prajakta P. Baikar; Guruprasad R. Mavlankar; Deepa N. Rangadal; Minakshi N. Bhatu; Shubhangi P. Patil (Next Research, 2024)

Cinnamon essential oil incorporated chitosan submicron emulsion as a sustainable alternative for extension of mango shelf life - Vinayak V. Deshi; Mallikarjun G. Awati; Deepa Terdal; S.N. Patil; Anita R. Ghandhe; Avinash S. Gudigennavar; Pooja Patalli; Deep Lata; Duniya Ram Singh; Mohammed Wasim Siddiqui (Sustainable Chemistry and Pharmacy, 2024)

Effects of Dietary Zinc Deficiency and Supplementation on Prepubertal Rat Testes: Sulfhydryl and Antioxidant Status - Deepa Kumari; Neena Nair; R. S. Bedwal (Indian Journal of Clinical Biochemistry, 2024)

Diagnostic efficacy of urinary neutrophil gelatinase-associated lipocalin and kidney injury molecule-1 for early detection of acute kidney injury in dogs with leptospirosis or babesiosis - M. Asma Idress; P. M. Deepa; R. L. Rathish; K. Vinodkumar; M. Pradeep (Veterinary Research Communications, 2024)

Targeting lipid-sensing nuclear receptors PPAR (α, γ, β/δ): HTVS and molecular docking/dynamics analysis of pharmacological ligands as potential pan-PPAR agonists - Sumit Kumar Mandal; Sonakshi Puri; Banoth Karan Kumar; Mohammed Muzaffar-Ur-Rehman; Pankaj Kumar Sharma; Murugesan Sankaranarayanan; P. R. Deepa (Molecular Diversity, 2024)

Overview of applications of near infrared (NIR) spectroscopy in wood science: recent advances and future prospects - M. S. Deepa; S. R. Shukla; B. U. Kelkar (Journal of the Indian Academy of Wood Science, 2024)

Above and below-ground bacterial communities shift in seagrass beds with warmer temperatures - Luke DA. Walker; Paul E. Gribben; Tim M. Glasby; Ezequiel M. Marzinelli; Deepa R. Varkey; Katherine A. Dafforn (Frontiers in Marine Science, 2024)
Current rates of ocean warming are predicted to exacerbate ongoing declines in seagrass populations. Above-ground responses of seagrass to increasing temperatures have been studied from a direct physiological perspective while indirect effects, including changes to microbially-mediated below-ground processes, remain poorly understood. To test potential effects of increased temperature on seagrass growth and associated microbial communities, we sampled seagrass beds experiencing ambient and elevated water temperatures at Lake Macquarie, Australia. Sites with warmer water were associated with a plume from a power station discharge channel with temperatures analogous to conditions predicted by 2100 under current rates of ocean warming (+3°C). The microbial community composition in both sediments and leaf tissues varied significantly between warm and ambient water temperatures with higher relative abundances of putative sulphate-reducing bacteria such as Desulfocapsaceae, Desulfobulbaceae and Desulfosarcinaceae in sedimentary communities in warm water. Above-ground biomass and seagrass growth rates were greater at warm sites while below-ground biomass and detrital decomposition rates showed no difference suggesting potential buffering of temperature effects below-ground. These findings suggest a 3°C rise in temperate regions is unlikely to induce mortality in seagrass however, it may shift microbial communities towards more homogenous structure and composition.

A systematic review of regional and global climate extremes in CMIP6 models under shared socio-economic pathways - R. Deepa; Vinay Kumar; Suchithra Sundaram (Theoretical and Applied Climatology, 2024)

Phenotypic diversity in Tamarindus indica L. sourced from different provenances in India - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; K. Prakash (Agroforestry Systems, 2024)

Nitrogen-cycling genes in oyster reefs and surrounding sediments: Relationships with environmental factors and respective nitrogen rates - Giulia Filippini; Ana B. Bugnot; Deepa R. Varkey; Nachshon Siboni; Angus Ferguson; Paul E. Gribben; Katherine Erickson; Julia Palmer; Katherine A. Dafforn (Marine Pollution Bulletin, 2023)

Nutraceutical and flavor profiles in underutilized desert legumes of India: gene editing strategies towards sustainable food development - Tripti Joshi; Hansa Sehgal; Sumit Kumar Mandal; Mukul Joshi; P. R. Deepa; Pankaj Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2023)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Beneficial role of kaempferol and its derivatives from different plant sources on respiratory diseases in experimental models - Sehal Mishra; Deepa Gandhi; Rajnarayan R. Tiwari; Subbiah Rajasekaran (Inflammopharmacology, 2023)

Graph neural network-based remote target classification in hyperspectral imaging - R. Niruban; R. Deepa (International Journal of Remote Sensing, 2023)

Sleep and Autism Spectrum Disorder: A Comprehensive Review of Diagnosis, Markers, Interventions, and Treatments - Deepa Burman; Karthikeyan Ramanujam; Dilshad Manzar; Vijay Kumar Chattu; David Warren Spence; Nevin F. W. Zaki; Haitham Jahrami; Seithikurippu R. Pandi-Perumal (Sleep and Vigilance, 2023)

Adsorptive removal of tetracycline from aqueous solutions using magnetic Fe2O3 / activated carbon prepared from Cynometra ramiflora fruit waste - Raja Selvaraj; Deepa Prabhu; P. Senthil Kumar; Gayathri Rangasamy; Gokulakrishnan Murugesan; Mouli Rajesh; Louella Concepta Goveas; Thivaharan Varadavenkatesan; Adithya Samanth; R. Balakrishnaraja; Ramesh Vinayagam (Chemosphere, 2023)

Effect of Different Proportions of Phenolics on Antioxidant Potential: Pointers for Bioactive Synergy/Antagonism in Foods and Nutraceuticals - Tripti Joshi; P. R. Deepa; Pankaj Kumar Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Galactosylgalactosylxylosylprotein 3-beta-glucuronosyltransferase—a potent biomarker for the diagnosis of tuberculosis in elephants - Ranjini Manuel; P. M. Deepa; R. U. Ashok; Rajeshkumar; K. Vijayakumar; K. Karthiayini; A. Janus (European Journal of Wildlife Research, 2022)

Sequential Profiling of Anti-SARS CoV-2 IgG Antibody in Post COVID-19 Patients - Ajaikumar Sukumaran; Rhema Elizabeth Thomas; R. Arun Krishnan; Thushara Thomas; Riji Thomas; Deepa K. Vijayan; Jofy. K. Paul; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2022)

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

Impact of weather parameters on the development of bacterial leaf spot in bottle gourd and pumpkin - Kumud Jarial; R. S. Jarial; Sujata Kumari; Arpana Sharma; Deepa Sharma (Indian Phytopathology, 2022)

A New Semi-automated Algorithm for Volumetric Segmentation of the Left Ventricle in Temporal 3D Echocardiography Sequences - Deepa Krishnaswamy; Abhilash R. Hareendranathan; Tan Suwatanaviroj; Pierre Boulanger; Harald Becher; Michelle Noga; Kumaradevan Punithakumar (Cardiovascular Engineering and Technology, 2022)

Silent metabolism and not-so-silent biological activity: possible molecular mechanisms of stress response in edible desert legumes - Vidushi Asati; P. R. Deepa; Pankaj Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2021)

Investigation of Kinetic Drug Release Characteristics and In Vitro Evaluation of Sustained-Release Matrix Tablets of a Selective COX-2 Inhibitor for Rheumatic Diseases - M. Karthikeyan; M. K. Deepa; E. Bassim; C. S. Rahna; K. R. Sree Raj (Journal of Pharmaceutical Innovation, 2021)

Atmospheric Aerosol Scattering Coefficients in a Broad Visible Spectral Region - R. Arun; P. Anoop; S. John; J. Chen; V. Deepa; R. Varma (Aerosol Science and Engineering, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Bioplastic production from renewable lignocellulosic feedstocks: a review - R. Reshmy; Deepa Thomas; Eapen Philip; Sherely A. Paul; Aravind Madhavan; Raveendran Sindhu; Ranjna Sirohi; Sunita Varjani; Arivalagan Pugazhendhi; Ashok Pandey; Parameswaran Binod (Reviews in Environmental Science and Bio/Technology, 2021)

Optimization and scale-up of laccase production by Bacillus sp. BAB-4151 isolated from the waste of the soap industry - T. Deepa; A. K. Gangwane; R. Z. Sayyed; H. P. Jadhav; Mehjabeen (Environmental Sustainability, 2020)

Evaluation of oxidative stress in caprine anaplasmosis and effect of vitamin E–selenium in monitoring oxidative stress - G. Dhanasree; Usha Narayana Pillai; Chirayath Deepa; V. R. Ambily; M. Shynu; C. Sunanda (Tropical Animal Health and Production, 2020)

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

Calcium alginate encapsulated synthetic seed production in Plumbago rosea L. for germplasm exchange and distribution - Anand Vishnu Prakash; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. R. Reghunath (Physiology and Molecular Biology of Plants, 2018)

The interannual sea level variability in the Indian Ocean as simulated by an Ocean General Circulation Model - J. S. Deepa; C. Gnanaseelan; R. Kakatkar; A. Parekh; J. S. Chowdary (International Journal of Climatology, 2018)
Limited coverage of tide gauge observations and limited length record of altimeter observations remain inadequate for the Indian Ocean sea level variability studies especially for longer periods. This study takes advantage of Ocean General Circulation Model (OGCM) simulations and ocean reanalysis to explore the interannual variability of sea level in the Indian Ocean. The model simulated sea level anomalies display good correlation with altimetry and reanalysis products. This consistency in model simulations with observations and reanalysis highlights the potential use of this OGCM in understanding the sea level variability. Analysis reveals that co‐occurrence years (years when Indian Ocean Dipole (IOD) and El Niño events co‐occur) contribute significantly towards the interannual variability in the Indian Ocean compared to pure IOD or El Niño events, and are characterized by persistent generation of open ocean downwelling, with maximum signals in the 10° to 5°S region. The OGCM experiments are carried out by modulating the forcing fields over the Pacific and the Indian Ocean to understand the physical mechanisms causing sea level variability. The experiments suggest that the remote forcing from the Pacific Ocean via Indonesian ThroughFlow (ITF) induce significant sea level changes in the southern Indian Ocean only with variability mostly in the decadal time scales and the northern and equatorial Indian Ocean are not affected by ITF. This study also shows that El Niño and IOD‐induced variations in zonal wind stress and wind stress curl mainly contribute the interannual sea level variations in the Indian Ocean. The forcing associated with the co‐occurrence years are multi‐phased with coastal and open ocean forcing. Whereas the pure IOD and El Nino forcing is mainly found only over the open ocean. The decadal variability in the ENSO is primarily responsible for the decadal sea level variability in the Indian Ocean by modulating ITF transport.

Isolation and Characterization of Fusarium verticillioides NKF1 for Unsaturated Fatty Acid Production - R. Manjoo; S. Deepa; Alok K. Yadav; Nand K. Singh (Current Microbiology, 2017)

Microbial population shift caused by sulfamethoxazole in engineered-Soil Aquifer Treatment (e-SAT) system - Ashwinkumar P. Rudrashetti; Niti B. Jadeja; Deepa Gandhi; Asha A. Juwarkar; Abhinav Sharma; Atya Kapley; R. A. Pandey (World Journal of Microbiology and Biotechnology, 2017)

Groundwater recharge potential zones mapping in upper Manimuktha Sub basin Vellar river Tamil Nadu India using GIS and remote sensing techniques - S. Deepa; S. Venkateswaran; R. Ayyandurai; R. Kannan; M. Vijay Prabhu (Modeling Earth Systems and Environment, 2016)

Comparative Transcriptome Analysis of Two Species of Curcuma Contrasting in a High-Value Compound Curcumin: Insights into Genetic Basis and Regulation of Biosynthesis - T. E. Sheeja; K. Deepa; R. Santhi; B. Sasikumar (Plant Molecular Biology Reporter, 2015)

Acute Toxicity Assessment of Reactive Red 120 to Certain Aquatic Organisms - R. Darsana; G. Chandrasehar; V. Deepa; Y. Gowthami; T. Chitrikha; S. Ayyappan; A. Goparaju (Bulletin of Environmental Contamination and Toxicology, 2015)

Environmental effects on germination phenology of co-occurring eucalypts: implications for regeneration under climate change - Deepa S. Rawal; Sabine Kasel; Marie R. Keatley; Craig R. Nitschke (International Journal of Biometeorology, 2015)

An exploratory analysis linking neuropsychological testing to quantification of tractography using High Definition Fiber Tracking (HDFT) in military TBI - Nora Presson; Sue R. Beers; Lisa Morrow; Lauren M. Wagener; William A. Bird; Gina Van Eman; Deepa Krishnaswamy; Joshua Penderville; Allison J. Borrasso; Steven Benso; Ava Puccio; Catherine Fissell; et al. (Brain Imaging and Behavior, 2015)

Fructose induces mitochondrial dysfunction and triggers apoptosis in skeletal muscle cells by provoking oxidative stress - Natasha Jaiswal; Chandan K. Maurya; Deepti Arha; Deepa R. Avisetti; Ayyappan Prathapan; Palayyan S. Raj; Kozhiparambil G. Raghu; Shasi V. Kalivendi; Akhilesh Kumar Tamrakar (Apoptosis, 2015)

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

Indian summer monsoon onset vortex formation during recent decades - R. Deepa; Jai Ho Oh (Theoretical and Applied Climatology, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Environmental effects on growth phenology of co-occurring Eucalyptus species - Deepa S. Rawal; Sabine Kasel; Marie R. Keatley; Cristina Aponte; Craig R. Nitschke (International Journal of Biometeorology, 2014)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

A Model Study on Understanding the Influence of Arabian Sea Mini Warm Pool on Monsoon Onset Vortex Formation - R. Deepa; C. Gnanaseelan; M. Deshpande; P. S. Salvekar (Pure and Applied Geophysics, 2012)

A Web GIS Application for Dams and Drought in India - Devendra Singh Rathore; Deepa Chalisgaonkar; R. P. Pandey; Tanvear Ahmad; Yatveer Singh (Journal of the Indian Society of Remote Sensing, 2010)

On the relationship between Arabian Sea warm pool and formation of onset vortex over east-central Arabian Sea - R. Deepa; C. Gnanaseelan; P. Seetaramayya; S. G. Nagar (Meteorology and Atmospheric Physics, 2010)

Cryoconservation and regeneration of axillary shoot meristems of Indigofera tinctoria (L.) by encapsulation–dehydration technique - Deepa S. Nair; B. R. Reghunath (In Vitro Cellular & Developmental Biology - Plant, 2009)

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango - K. Usha; B. Singh; P. Praseetha; N. Deepa; D. K. Agarwal; R. Agarwal; A. Nagaraja (European Journal of Plant Pathology, 2009)

Purification and characterization of phycoferritin from the blue-green alga, Arthrospira (Spirulina) platensis - G. Lakshmi Deepa; R. B. Sashidhar; Vijay Deshpande (Journal of Applied Phycology, 2008)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)

CancerLectinDB: a database of lectins relevant to cancer - Deepa Damodaran; Justin Jeyakani; Alok Chauhan; Nirmal Kumar; Nagasuma R. Chandra; Avadhesha Surolia (Glycoconjugate Journal, 2008)

Structure of the extended diarrhea-inducing domain of rotavirus enterotoxigenic protein NSP4 - R. Deepa; C. Durga Rao; K. Suguna (Archives of Virology, 2007)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

STUDIES ON NOVEL NON-IMIDAZOLE HUMAN H4 RECEPTOR ANTAGONISTS USING GFA AND FREE-WILSON ANALYSIS - Surekha R. Pimple; Mandar A. Kelkar; Deepa V. Pednekar; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

3D QSAR STUDIES OF INHIBITORS OF EPIDERMAL GROWTH FACTOR RECEPTOR [EGFR] USING CoMFA AND GFA METHODOLOGIES - Deepa V. Pednekar; Mandar A. Kelkar; Surekha R. Pimple; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

3D QSAR STUDIES OF INHIBITORS OF CHOLESTEROL ESTER TRANSFER PROTEIN (CETP) BY CoMFA, CoMSIA AND GFA METHODOLOGIES - Mandar A. Kelkar; Deepa V. Pednekar; Surekha R. Pimple; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

The Effect of Hematocrit and Leukocyte Adherence on Flow Direction in the Microcirculation - Michael R. King; Deepa Bansal; Michael B. Kim; Ingrid H. Sarelius (Annals of Biomedical Engineering, 2004)

The potential role of sialoadhesin as a macrophage recognition molecule in health and disease - Paul R Crocker; Adele Hartnell; James Munday; Deepa Nath (Glycoconjugate Journal, 1997)